Pola Komunikasi Organisasi Kepemimpinan PT. Bank Syariah Indonesia KCP Tangerang Tanah Tinggi - Irwanda, Andri; Mirza, Mochammad; Alamsyah, Alamsyah; Suseno, Ari (Institut Agama Islam Sunan Giri Ponorogo, 2024)
An organization must strive to create a working environment where leaders and employees feel comfortable with each other. To this goal, leaders who have the power and ability to inspire their colleagues to do better in their work. Good leaders have the ability to give direction, correction, and evaluation to their subordinates to help them the goals of the organization. This research is categorized into exploratory research followed by descriptive research. Explorative research is an early study aimed at obtaining an idea of a subject of research that will be further studied. Descriptive study is a study whose purpose is to show (describe) something, and is non-experimental because the research is not under the direct control of the researcher.In delineating the communication patterns at BSI PT KCP Tangerang Terra Alto, the results of qualitative findings from in-depth interviews with employees and leaders describe the application of various forms of communication. Some respondents stated that face-to-face meetings provided opportunities for non-verbal expression and strengthened team members' connections. In the context of evaluating the effectiveness of communication, observational data show that the level of employee participation in policy discussions and implementation is a key indicator. In an in-depth study of the organizational communication and leadership patterns at PT Bank Syariah Indonesia (BSI) KCP Tangerang Tanah High, the data findings describe the diversity and complexity of the internal dynamics of the organization. Adopting a holistic approach in the type of communication, involving both formal and informal elements, provides room for creative exchange of ideas. Despite the dominant digital media, the value of face-to-face meetings remains significant, enabling non-verbal expression and strengthening interpersonal connections. From these findings, it can be concluded that organizations face complex challenges in managing communication and leadership patterns. Strategic recommendations include optimizing leadership styles, developing communication skills, and setting up forums for exchange of ideas.